2011
DOI: 10.1098/rspb.2011.2237
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection favours male parental care, when females can choose

Abstract: Explaining the evolution of male care has proved difficult. Recent theory predicts that female promiscuity and sexual selection on males inherently disfavour male care. In sharp contrast to these expectations, male-only care is often found in species with high extra-pair paternity and striking variation in mating success, where current theory predicts female-only care. Using a model that examines the coevolution of male care, female care and female choice; I show that inter-sexual selection can drive the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 33 publications
3
75
0
1
Order By: Relevance
“…However, in organisms with males that provide some parental care, there is a debate whether this is important to population growth (Steinhart et al 2004). This is particularly relevant to fish ecology, where there are numerous examples of males providing parental care in marine and freshwater systems (Alonzo 2012). Thus, the effects of contaminants on male parental care could be quite detrimental to this particularly diverse and abundant taxonomic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in organisms with males that provide some parental care, there is a debate whether this is important to population growth (Steinhart et al 2004). This is particularly relevant to fish ecology, where there are numerous examples of males providing parental care in marine and freshwater systems (Alonzo 2012). Thus, the effects of contaminants on male parental care could be quite detrimental to this particularly diverse and abundant taxonomic group.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired reproductive output due to contaminants may scale up to ecosystem processes and also affect the ability of fisheries to respond to harvest. Given that environmental endocrine disruptors and estrogen mimics are a persistent problem in aquatic ecosystems, these hidden effects on reproduction need to be incorporated into predictive models, and male contributions to reproduction, especially in populations where males rely on complex mechanisms through sexual selection including attracting females (Alonzo 2012), should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, observational and experimental evidence for these animal groups clearly show that providing paternal care and acquiring new mates are non-mutually exclusive activities [18][19][20]. Moreover, theoretical studies have suggested that female preferences for caring males have played an important role in the evolution of paternal care [18,[21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although many theoretical models predict that the maintenance of parental care depends on the balance between costs and benefits of this behavior to the parents [2,20,22], empirical information among arthropods is restricted mostly to species exhibiting maternal care [e.g., 6-8, but see 9, 16]. In this paper, we used the Neotropical harvestman Iporangaia pustulosa (Arachnida: Opiliones) as a model organism to assess energetic and survival costs of male egg-guarding behavior under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Após adquirir um ninho, um macho é visitado por uma ou mais fêmeas que, em teoria, poderiam usar o tamanho do detentor do ninho como indicador de sua qualidade genética ou da sua habilidade como defensor da prole (Tallamy, 2001;Alonzo, 2012).…”
Section: Discussionunclassified